2016
DOI: 10.1186/s12866-016-0792-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis by RNAseq of necrotic enteritis Clostridium perfringens during in vivo colonization and in vitro conditions

Abstract: BackgroundNecrotic enteritis (NE) caused by netB-positive type A Clostridium perfringens is an important bacterial disease of poultry. Through its complex regulatory system, C. perfringens orchestrates the expression of a collection of toxins and extracellular enzymes that are crucial for the development of the disease; environmental conditions play an important role in their regulation. In this study, and for the first time, global transcriptomic analysis was performed on ligated intestinal loops in chickens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Previous studies have examined the transcriptomes of regulatory mutants of C. perfringens JIR325 in vitro ( 33 ), of an avian necrotic enteritis strain in chicken intestinal loops ( 34 ), and of a C. perfringens biofilm ( 35 ). We compared the in vivo bacterial gene expression levels with the expression levels from the equivalent in vitro broth cultures, which represents the first time that the transcriptome of C. perfringens cells in a myonecrosis infection has been examined.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have examined the transcriptomes of regulatory mutants of C. perfringens JIR325 in vitro ( 33 ), of an avian necrotic enteritis strain in chicken intestinal loops ( 34 ), and of a C. perfringens biofilm ( 35 ). We compared the in vivo bacterial gene expression levels with the expression levels from the equivalent in vitro broth cultures, which represents the first time that the transcriptome of C. perfringens cells in a myonecrosis infection has been examined.…”
Section: Resultsmentioning
confidence: 99%
“…Other virulence factors may additively contribute to the CP pathogenesis in NE induction. Global transcriptomic analysis performed on ligated intestinal loops in chickens following infection with a netB + CP strain revealed that numerous virulence factors were significantly expressed in vivo, such as cpa, netB and sialidase genes [ 19 ]. Del1 strain is a virulent strain isolated from a field disease outbreak to be used as a challenge strain.…”
Section: Resultsmentioning
confidence: 99%
“…p -value or q -value were used to conduct significance analysis. Parameters for classifying significantly DEGs are ≄2-fold differences (|log 2 FC|≄1, FC: the fold change of expressions) in the transcript abundance and q < 0.05 (Parreira et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…The best matches were selected to annotate the DEGs. Finally, DEGs were subjected to GO functional analysis and KEGG, utilizing default parameters, to annotate the DEGs' major GO, and KEGG categories (Liu et al, 2014 ; Parreira et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%